2020
DOI: 10.1111/saje.12270
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19, Economic Growth and South African Fiscal Policy

Abstract: Following years of fast‐rising debt levels, we show that the Covid‐19 crisis worsened an already deteriorating fiscal position in South Africa. To restore fiscal sustainability in the aftermath of the crisis some commentators argue that higher government expenditure will grow GDP sufficiently to stabilise the debt/GDP ratio. We reject this, showing that although a real increase in expenditure stimulates economic growth (a short‐run, once‐off effect), the public expenditure/GDP ratio exceeds the level at which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
2
38
0
2
Order By: Relevance
“…The COVID-19 crisis sparked worldwide and quick policy response measures around the world. These are anchored on preventative and palliative health measures and wideranging macroeconomic policy measures such as fiscal and monetary aid to businesses reeling under the impacts of the pandemic (Burger and Calitz 2021). This study looks solely at fiscal responses to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 crisis sparked worldwide and quick policy response measures around the world. These are anchored on preventative and palliative health measures and wideranging macroeconomic policy measures such as fiscal and monetary aid to businesses reeling under the impacts of the pandemic (Burger and Calitz 2021). This study looks solely at fiscal responses to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Ф. Бургером и Э. Калицем [6] на примере ЮАР рассматриваются экономические, в том числе фискальные меры, принимаемые в условиях коронакризиса. К последним отнесены: отсрочки налоговых платежей и налоговые каникулы; поддержка малого и среднего бизнеса, домохозяйств, здравоохранения и других важных отраслей, муниципалитетов.…”
Section: результаты и дискуссияunclassified
“…For the economic impact of Covid-19, Burger and Calitz ( 5 ) find that Covid-19 exacerbated South Africa fiscal position. While higher government spending helped to restore GDP and maintain debt/GDP stability, the empirical study found that the public spending/GDP ratio exceeded the level at which an increase in that ratio would have positively affected growth.…”
Section: Literature Reviewmentioning
confidence: 99%